The effects of storage temperatures and pretreatments on the germination of azarole (Crataegus azarolus var. pontica) seeds : Utjecaj temperature čuvanja i predsjetvene pripreme na klijavost sjemena mušmulastog gloga (Crataegus azarolus var. pontica) - Gokturk, Askin (Array, 2021)
In this study, which aimed to determine the effects of storage temperatures on the germination of azarole (Crataegus azarolus var. pontica) seeds, pretreatments were applied to the seeds and were dry-stored for 10 months at four storage temperatures (-5, 5, 15 and 25ºC) for various periods in floating water and in an ash solution (2, 4 and 6 days), scarification in sulfuric acid (1, 3 and 6 hours), and combinations of scarification in sulfuric acid and floating in ash solution pretreatments. Also, the scarification rates in the seed coats that were corroded in sulfuric acid for 1, 3 and 6 hours were determined. The experimental design was a randomized complete block with four replications. As a result of the study, higher germination percentages (p<0.05) were achieved (20.95%) in seeds stored at 15ºC. The results show that the scarification in sulfuric acid is more effective (p>0.05) on the germination percentage of azarole seeds. The diameters of the seeds that were corroded in sulfuric acid for 1, 3 and 6 hours decreased by 6.15%, 10.47% and 11.51%, respectively. To achieve higher germination percentages, azarole seeds should be kept at 15ºC, and exposed to sulfuric acid for 3 hours with 4 day ash solution for sowing in August.